Clothing needs and preferences of a selected group of Filipino elderly - Rodriguez, Ma. Jihanna E.
In the Philippines, while there has been a general concern on the elderly, very little interes has been shown especially in the field of clothing. Nowadays, the clothing market has been focusing more on the younger generations. This study was intended to determine the needs and preferences in clothing of a selected group of Filipino elderly. The research method used in this study was the descriptive type. Answers to the questions were obtained through a survey. Difficulties in locating and estimating the age of prospective respondents were faced by the researcher. Because of this, the researcher coordinated with organizations for the elderly, namely the Gintong Samahan ng UP and UP Village Senior Citizens Association. A selected number of elderly working and residing in UP Campus, Novaliches and Fairview, were also chosen as respondents. A total of 55 respondents participated in the study. Frequency counts